Kebersyukuran dan Kemaafan Terhadap Kepuasan Pernikahan - Herawati, Icha; Widiantoro, Didik (UIR Press, 2019)
Marital satisfaction is an important aspect of the couple in the marriage. This study aims to look at the relationship between gratitude and forgiveness to marital satisfaction. This research was conducted in quantitative research using a research scale. The study population is a married couple who are residents of Rokan Hulu Regency. A purposive sampling technique was used in this study to determine respondents in accordance with research needs. The research subjects consisted of 330 respondents, 156 male respondents and 175 female respondents. The research scale in this study consisted of the gratitude scale, the scale of forgiveness, and the scale of marital satisfaction. The results showed that there was a significant relationship between gratitude and forgiveness to the marriage satisfaction of the people of Rokan Hulu Regency. The expected target output in this study is that rural communities are more aware of marital satisfaction, gratitude, and forgiveness. The results of this study can also be used as a reference regarding the household life of the Rokan Hulu community and as psychoeducation for married couples.